(untitled) (Al-Mansour Journal, 2022)
There are certain changes related to the extension of management’s assignments to strategic areas which is closely connected with increasing influence of numerous factors such as the rapid growth of innovation, the continuous technical development acceleration, and extension of competition arena among business organizations. These changes force management to adopt approaches based on concepts that are characterized by strategic view. Among these concepts, one can make use of value creation concept. The research aims at presenting and analyzing contemporary approaches based on concepts that provide intellectual bases of strategic view in administrating expected future costs, since the survival and success of business units constitute a function of the methods of understanding, analyzing, and applying those approaches and concepts which the business units adopt. The research reaches at a number of conclusions concerning the concepts that seek value creation for the shareholder which take the form of either paid dividends or gained capital added to the shareholder’s equity, or sometimes, both these forms are adopted. The research points out the importance of these concepts and approaches to support the role of managerial accounting in terms of using them within the so called framework of "value pyramid". All this should provide a valid basis for the application of value-based management